2007
DOI: 10.1158/0008-5472.can-06-3456
|View full text |Cite
|
Sign up to set email alerts
|

Human Tumor-Derived Exosomes Selectively Impair Lymphocyte Responses to Interleukin-2

Abstract: Exosomes are nanometer-sized vesicles, secreted by normal and neoplastic cells. The outcome following interaction between the cellular immune system and cancer-derived exosomes is not well understood. Interleukin-2 (IL-2) is a key factor supporting expansion and differentiation of CTL and natural killer (NK) cells but can also support regulatory T cells and their suppressive functions. Our study examined whether tumor-derived exosomes could modify lymphocyte IL-2 responses. Proliferation of healthy donor perip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
386
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(398 citation statements)
references
References 40 publications
10
386
0
2
Order By: Relevance
“…Exosomes originating from immune cells routinely carry a host of immunoregulatory proteins, such as cytokines (e.g., TNF-α, IL-1, IL-18, etc.) (Clayton et al, 2007;Turola et al, 2012). Of interest, a large portion of proteins in exosomes are found polyubiquitinated (Luzio et al, 2009), suggesting that exosomal proteins are subjected to protein degradation by lysosomal enzymes unless they are released to the extracellular space following fusion of the late endosomes to the plasma membrane Exosomes as a carrier of RNAs Besides proteins, exosomes also carry nucleic acids (Chaput and Thery, 2011;Zomer et al, 2010).…”
Section: Molecular Composition Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes originating from immune cells routinely carry a host of immunoregulatory proteins, such as cytokines (e.g., TNF-α, IL-1, IL-18, etc.) (Clayton et al, 2007;Turola et al, 2012). Of interest, a large portion of proteins in exosomes are found polyubiquitinated (Luzio et al, 2009), suggesting that exosomal proteins are subjected to protein degradation by lysosomal enzymes unless they are released to the extracellular space following fusion of the late endosomes to the plasma membrane Exosomes as a carrier of RNAs Besides proteins, exosomes also carry nucleic acids (Chaput and Thery, 2011;Zomer et al, 2010).…”
Section: Molecular Composition Of Exosomesmentioning
confidence: 99%
“…Exosomes from tumor cells can have effects on immune cells, resulting in promotion or suppression of the host immunity to the tumor (Clayton et al, 2007;Filipazzi et al, 2012;Gastpar et al, 2005;Taylor and Gercel-Taylor, 2011). Earlier studies showed that immunization of mice with exosomes prepared from tumor cells reduced the growth of implanted tumor cells.…”
Section: Physiological (Immunological) Roles Of Exosomesmentioning
confidence: 99%
“…It is thought the contents of exosomes depend on their cell of origin [78]; those derived from immune cells having immunostimulatory and anti-tumor effects in vivo [89], while those derived from tumor cells accelerate tumor growth [78,90] and invasiveness [91,92]. Additionally, the RNA contained within exosomes is amplifiable; suggesting protection from RNase degradation by the exosome membrane [78].…”
Section: Origin Of Extracellular Nucleic Acidsmentioning
confidence: 99%
“…Exosomes have also been described as having both immunostimulatory and anti-tumour affects in vivo (7). Exosomes derived from tumour cells have been associated with accelerating tumour growth (6,8) and invasiveness (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%